An evaluation of solar thermal heating to support a freeze-thaw anaerobic digestion system for human waste treatment in subarctic environments. (October 2022) - Krause, Max J.; Detwiler, Natalie; Schwarber, Amy; McCauley, Margaret
Abstract: Remote locations, small communities, and weather prohibit the operation of piped sanitary sewers in many Alaska Native Villages (ANVs). Research was conducted to understand the technical feasibility of installing anaerobic digesters (ADs) in remote ANVs which would be heated by solar thermal collectors. Biochemical methane potential (BMP) assays were conducted to understand the effect of freezing and thawing on methanogenic activity of synthetic human feces. BMPs were frozen at −20 or −80 °C for 7 days and then incubated at psychrophilic (20 °C) or mesophilic (37 °C) conditions. Psychrophilic BMPs frozen at −20 or −80 °C yielded 453 ± 119 and 662 ± 77 mL CH4 /g VS, respectively. Mesophilic BMPs frozen at −20 or −80 °C yielded 337 ± 59 and 495 ± 63 mL CH4 /g VS, respectively. Freezing caused a lag period, but ultimately many of the assays reached yields similar to or even greater than the baseline, unfrozen assays. Monthly solar radiation and air temperature data were used to identify the number of solar thermal collectors that would be required to supplement heat energy to operate the ADs in several locations. Alaskan subarctic locations receive enough solar thermal energy in summer months to support seasonally operated, psychrophilic ADs. Graphical abstract: Image 1